2018
DOI: 10.1097/md.0000000000011736
|View full text |Cite
|
Sign up to set email alerts
|

Direct costs associated with adverse events of systemic therapies for advanced melanoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
2
14
0
1
Order By: Relevance
“…8 Among these therapies, dacarbazine is reported to cause pain symptoms in animal models 10 and oncological patients. 3,31 In the present study, dacarbazine stimulated TRPA1 in cultured mouse DRG neurons and in hTRPA1-HEK293 cells, effects that were abolished by a TRPA1 antagonist. Moreover, we demonstrated that dacarbazine caused mechanical and cold allodynia in mice by TRPA1 activation and sensitization, which was reduced by TRPA1 pharmacological blockade, antioxidants and by TRPA1 gene deletion or silencing.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…8 Among these therapies, dacarbazine is reported to cause pain symptoms in animal models 10 and oncological patients. 3,31 In the present study, dacarbazine stimulated TRPA1 in cultured mouse DRG neurons and in hTRPA1-HEK293 cells, effects that were abolished by a TRPA1 antagonist. Moreover, we demonstrated that dacarbazine caused mechanical and cold allodynia in mice by TRPA1 activation and sensitization, which was reduced by TRPA1 pharmacological blockade, antioxidants and by TRPA1 gene deletion or silencing.…”
Section: Discussionsupporting
confidence: 50%
“…Antineoplastic therapy has been associated with the development of pain syndrome, which puts limits to its use and compromises the patient's quality of life . Among these therapies, dacarbazine is reported to cause pain symptoms in animal models and oncological patients . In the present study, dacarbazine stimulated TRPA1 in cultured mouse DRG neurons and in hTRPA1‐HEK293 cells, effects that were abolished by a TRPA1 antagonist.…”
Section: Discussionmentioning
confidence: 53%
“…e monetary costs associated with trAEs were assumed to be primarily those resulting from hospitalization costs. ese were estimated as weighted averages of the costs associated with specific grades 3-4 trAEs and the frequency of occurrence of those events in the respective trials [22,33,34,44,45]. Hospitalization due to trAEs was assumed to occur for grades 3-4 only, at a rate that was estimated using insurance claims data [4].…”
Section: Estimates Of Costs and Quality Of Lifementioning
confidence: 99%
“…However,t he patients may be at serious risko fk illing normalc ells, developing secondary cancer, and overwhelmingi mmune systemsd ue to toxic side effects arising from nonspecific drug delivery and radiation damage. [4] Photothermalt herapy (PTT) has been developed into an effectivea pproach for cancer therapy that ablates cancer cells by using the heat generated from absorbed near-infrared( NIR) light energyw ith minimum damage fort he patient. [5] Meanwhile, NIR (l = 700-1100 nm) laser-based PTT is preferable due to the large tissue penetration depth of the NIR light, which can reach af ew centimeters.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, traditional therapies include surgery, radiotherapy, and chemotherapy. However, the patients may be at serious risk of killing normal cells, developing secondary cancer, and overwhelming immune systems due to toxic side effects arising from nonspecific drug delivery and radiation damage …”
Section: Introductionmentioning
confidence: 99%